THE EFFECT OF APPLYING EXAMPLES NON EXAMPLES METHOD ON STUDENTS’ ACHIEVEMENT IN WRITING PROCEDURE TEXT - Fauzi Rizki Ananda and Elia Masa Ginting (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2014)
This study is aimed to find out whether Examples Non Examples method significantly effects the students’ achievement in writing procedure text. This study was an experimental design. The population of the study was grade IX of SMP Pemda Lubuk Pakam. The classes were divided in two groups, namely Experimental and Control group. Experimental group was the class taught by applying Examples Non Examples method, while Control group was taught by Lecture method. In this study, writing test was used as the instrument of collecting the data. Both experimental and control group were asked to write procedure text in pre-test and post-test. The data obtained were analyzed statistically by t-test formula. The result got t-observed is higher than t-table (3.808 > 2.000) at the level significance 0.05 with the degree of freedom (df) 62. It means that the alternative hypothesis (Ha) is accepted and Examples non Examples method significantly effects students’ achievement in writing procedure text.